ПОБУДОВА НАВЧАЛЬНОГО ДИСТАНЦІЙНОГО ТРЕНАЖЕРА ДЛЯ ПІДГОТОВКИ ПЕРСОНАЛУ ЕНЕРГЕТИЧНОЇ ГАЛУЗІ - Гурєєв, В.O.; Сангінова, О.В. (Інститут електродинаміки Національної академії наук України, 2017)
The development of a training remote simulator for the staff skills and training for operational and dispatching personnel in the energy sector is consider, developed a fast-acting method for calculating the modes for remote simulators and the ways of developing a system of continuous training and advanced training in the distributed network of training centers are proposed. References 6, figures 4.